GEODYNAMIC SETTING OF GOLD ORE DEPOSITS OF THE NEOPROTEROZOIC BODAIBO TROUGH - Kuz'min M.I.; Spiridonov A.I.; Nemerov V.K.; Yarmolyuk V.V.; Ivanov A.I.; Mitrofanov G.L. (My University, 2006)
The aim of this work is to show that the formation of the unique Sukhoi Log deposit and other smaller gold ore deposits of the Bodaibo area was related to a series of geological and geodynamic events. Each of these events was determined by certain settings spanning giant territories in the southern framing of the Siberian Craton. All these independent events were separated by a time span of hundreds of millions of years. They did not affect the type, timing, and position of the subsequent geological processes.
Keywords: Sukhoi Log; Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская